Emerging Technologies: a systematic literature review to strengthen cybersecurity - Bermúdez Cavero, Alan Omar; Anaya Salazar, George Danny; Herrera Lazo, Veronica Daleska; Bendezu Huaroto, Jose Julio; Zegarra Castañeda, Giany (LACCEI, 2025)
This review aims to identify and collect current knowledge on how technologies such as artificial intelligence, machine learning, blockchain, IoT, and others can strengthen cybersecurity. Method: the PICO strategy and PRISMA diagram were used, 133 relevant articles were selected and analyzed from the SCOPUS database between the years 2019 to April 2024. The methods of this SLR included rigorous inclusion and exclusion criteria to ensure the relevance and quality of the studies analyzed. Results: within the present work the most widely used emerging technologies and their practical applications in cybersecurity are highlighted, identifying significant trends and patterns in the implementation of these technologies. Conclusions: the main current limitations are pointed out, such as the lack of standardization and the need for further empirical research, and key areas for future research are proposed, including the evaluation of the effectiveness of these technologies in different business contexts; this study provides a comprehensive and updated view that can guide both researchers and practitioners in the implementation of cybersecurity strategies based on emerging technologies, offering a solid foundation for improving defenses against increasingly sophisticated cyber threats.